Propuesta de una ruta metodológica para la acreditación de ensayos en el laboratorio de salud pública departamental del Amazonas (2022)
Being public health laboratories, reference laboratories and head of the laboratory network in their territories, it is of utmost importance that they can demonstrate technical competence, and this is achieved through the accreditation of tests given by the national accreditation body. The present work is presented as an orientation to create a methodological route for the accreditation of tests under the ISO / IEC 17025: 2017 standard, in the departmental public health laboratory of Amazonas (LSPDA). The information published by the National Accreditation Agency of Colombia is reviewed, based on the review, a matrix is ​​created to include the most relevant criteria, the matrix is ​​applied in the LSPDA. The results are consolidated, graphed and analyzed, and are the inputs to create a methodological route that describes the step by step that is considered to achieve the accreditation of trials.